Resiliency training in portuguese army basic instruction: the role of military cohesion, self-esteem and anxiety - Sales, Celia M. D. (2018)
The present study aims to explore the impact of military training on the psychological resilience of army recruits; the moderator role of other variables relevant for the military training (namely, group cohesion, self-esteem, and anxiety proneness) is also considered. A convenience sample of 104 military recruits was evaluated before and after the first six weeks of the Enlisted Basic General Military training. Although results showed a non significant global effect of the recruit training on resilience, individual changes in resilience levels between the beginning and the final of the training period seem to be moderately associated with participants' self-esteem and group cohesion perception. The results are discussed regarding to their implications in military training context.